Pengaruh Digital Marketing, Electronic Word of Mouth (E-WOM), dan Harga Terhadap Keputusan Pembelian Konsumen Deliwafa Store Kota Kediri - Arie Vidianti, Ferita; M Mustaqim (Universitas Nahdlatul Ulama Sidoarjo, 2025)
This research aims to examine the influence of digital marketing, E-WOM, and price on consumer purchasing decisions at Deliwafa Store in Kediri City. It uses a quantitative approach in the form of causal associative research. The focus of this research population is consumers of Deliwafa Store in Kediri City with a sample of 80 respondents. The technique used is non-probability sampling and instruments in the form of a Likert scale questionnaire and data analysis techniques in the form of multiple linear regression analysis. The results of the partial test of the digital marketing variable obtained a t-value (18.401) > t-table (1.991) and significance (0.000) < (0.05), the E-WOM variable with a t-value (9.432) > t-table (1.991) and significance (0.030) < (0.05), and the price variable with a t-value (2.527) > t-table (1.991) and significance (0.014) < (0.05), it can be stated that each independent variable has a positive and significant effect on purchasing decisions. The test results of the study show empirical evidence that the variables of digital marketing, E-WOM, and price partially and simultaneously have a positive and significant effect on the purchasing decisions of consumers at Deliwafa Store in Kediri City with a high coefficient of determination of 91.9%.